Associations of High-Density Lipoprotein Cholesterol and Framingham Cardiovascular Risk in African Type 2 Diabetics with Diabetic Retinopathy - (:unkn) unknown (My University, 2021)
Objectives: To assess the associations of high-density lipoprotein cholesterol (HDL-C) and Framingham cardiovascular (CVD) with diabetic retinopathy (DR). DR is the most frequent cause of visual disability (VD) worldwide.Methods: A cross-sectional study of random sample of 200 T2DM Central Africans. Socio-biographical, laboratory and eye examination main outcome measures were investigated using Tertiles of HDL-C (stratification = lowest <40 mg/dL, normal or intermediate = 40 - 74.9 mg/dL, highest ? 75 mg/dL) and Framingham risk stratification (<10% and ?10%) by logistic regression models.Results: Out of 200 T2DM patients, 120 (35.5%) had DR and out of DR patients, 116 (n = 96.7%) had VD. There was a significant U- shaped relationship between DR rates and HDL-C stratification. In the normal HDL-C group, elevated 8-hydroxydeoxyguanosine and 10-year Framingham risk > 10% were the significant independent determinants for DR. In the highest HDL-C group, smoking status and 10-year Framingham risk ? 10% were the significantly independent determinants for DR. In 10-year Framingham risk ? 10% group, smoking status, insulin resistance and increasing levels of HDL-C were the significant independent determinants for DR.Conclusion: DR and VD remain a public health problem in T2DM Central Africans. Some Central Africans with DR and VD appear to have higher HDL-C than T2DM Central Africans without DR and VD. HDL-C in T2DM patients with DR, may be more tightly controlled by genetic factors (black Bantu ethnicity) than the other lipoproteins as reported among Indians, African-Americans, and Japanese individuals. The most preventable environmental risk factors for DR were smoking status, global cardiovascular disease risk, insulin resistance and oxidative stress.
Keywords: African Research